Acute Hypobaric and Hypoxic Preconditioning Reduces Myocardial Ischemia-Reperfusion Injury in Rats. (17th March 2021) - Terada, Hirofumi; Hirata, Naoyuki; Sawashita, Yasuaki; Ohno, Sho; Yoshikawa, Yusuke; Yamakage, Michiaki
Abstract : Background . Chronic and/or intermittent exposure to hypobaric hypoxia reportedly exerts cardioprotective effects against ischemia-reperfusion injury. However, few studies have focused on the cardioprotective effects of acute and/or short-term hypobaric and hypoxic exposures. This study investigated the effects of acute hypobaric hypoxia on myocardial ischemia-reperfusion injury. Materials and Methods . Rats were assigned to groups receiving normobaric normoxia (NN group), hypobaric hypoxia (HH group), or normobaric hypoxia (NH group). HH group rats were exposed to 60.8 kPa and 12.6% fraction of inspired oxygen in a hypobaric chamber for 6 h. NH group rats were exposed to hypoxic conditions under normal pressure. After each exposure, 30 min of myocardial ischemia was followed by 60 min of reperfusion. Cardiac function and infarct size were determined after reperfusion. Expression of hypoxia-inducible factor 1 alpha (HIF1 α ) was also measured. Results . Cardiac function was better preserved in the HH and NH groups than in the NN group (p  < 0.01 each). Median infarct size/area at risk was significantly lower in the HH group (50%, interquartile range [IQR] 48–54%; p  < 0.01 vs. NN group) and NH group (45%, IQR 36–50%; p  < 0.01 vs. NN group) than in the NN group (72%, IQR 69–75%). HIF1 α expression was significantly higher in the HH group (p  < 0.05 vs. NN group) and NH group (p  < 0.01 vs. NN group) than in the NN group. Conclusions . Exposure to acute and/or short-term hypobaric and hypoxic conditions might exert cardioprotective effects against myocardial ischemia-reperfusion injury via HIF1 α modulation.